THE MONASTERY OF “NEW NEAMŢ” – THE SACRED RIVER THAT FLEW IN THE OCEAN OF ROMANIAN HISTORY - Stela GUŢANU (Studia Universitatis Babeş-Bolyai. Musica)
Sacred music is a field of culture that comprises the essential human values, which are able to build and perfect the complex cultural undertaking of the human life; it is an emotional illustration of the spirit. Through the truth it embodies, sacred music aspires to reflect man’s secret, inner soul. This is a part of the people’s psychic and spiritual life, through the feelings and the attitudes that it transmits.